Protocol for induction and study of DNA double-strand breaks in mammalian cells using PALM microdissection and expansion microscopy - Fernando Luna-Maldonado; Diego Oliva-Rico; Alejandro López-Saavedra; Aquetzalli Arenas-Hernández; Clementina Castro-Hernández; Juan Eduardo Rodriguez Gatica; Eloy-Andres Pérez-Yepez; José Díaz-Chávez; Luis A. Herrera (STAR Protocols, 2025)
Summary: We present a protocol to induce localized DNA double-strand breaks (DSBs) in mammalian monolayer cells, using the PALM MicroBeam microdissector, followed by high-resolution visualization through expansion microscopy (ExM). We describe steps for laser microirradiation, immunostaining, and gel embedding. The protocol enables 4.5-fold physical expansion and confocal imaging of DNA damage sites. We quantify nuclear and damage site expansion using Fiji by measuring nuclear area and cross-sectional fluorescence profiles. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.